2017
DOI: 10.18632/oncotarget.21507
|View full text |Cite
|
Sign up to set email alerts
|

Associations between novel genetic variants in the promoter region ofMALAT1and risk of colorectal cancer

Abstract: The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a well-known long non-coding RNA, is involved in pathogenesis and progress of multiple tumors. However, no study has been performed to investigate the relationship between the genetic variants in promoter region of MALAT1 and colorectal cancer risk. In this study, we conducted a two-stage case-control study to evaluate whether MALAT1 genetic variants were associated with colorectal cancer risk. We identified that a single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 56 publications
1
32
0
1
Order By: Relevance
“…In addition, the study from Li et al also confirmed the rs1194338 polymorphism (C>A) was significantly associated with a reduced risk of CRC, which is more obvious protection in the subgroup. Further analysis showed that although MALAT1 was over-expressed in CRC tissues, the expression difference was not significant between CC and AA genotype of rs1194338 in CRC tissues [38]. Similar to Li's study, we observed the expression of the MALAT1 in IS group was higher significantly than normal group, but expression difference between the AC/AA and CC genotype were not significant (figure 1).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the study from Li et al also confirmed the rs1194338 polymorphism (C>A) was significantly associated with a reduced risk of CRC, which is more obvious protection in the subgroup. Further analysis showed that although MALAT1 was over-expressed in CRC tissues, the expression difference was not significant between CC and AA genotype of rs1194338 in CRC tissues [38]. Similar to Li's study, we observed the expression of the MALAT1 in IS group was higher significantly than normal group, but expression difference between the AC/AA and CC genotype were not significant (figure 1).…”
Section: Discussionsupporting
confidence: 81%
“…It was reported that genetic variation in promoter region will in uence transcriptome expression, stability and subcellular localization, leading to functional changes and the occurrence of disease [42]. However, rs1194338 polymorphism did not alter the MALAT1 expression levels in colorectal cancer tissues [26]. In addition, there was no statistically signi cant difference in MALAT1 expression between CC genotype and AA genotype [43].…”
Section: Discussionmentioning
confidence: 90%
“…Based on the selection criteria, 12 studies [17][18][19][20][21][25][26][27][28][29][30][31] were included in this meta-analysis ( Fig. 1).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…This suggested there was an interactive function between rs1194338 and the environment, whether it interacts with the environment in IS remains to be further explored. In colorectal cancer, previous study found carriers with AA and AC genotype of the rs1194338 were lower risk than CC genotype, and the conclusion from Li's study showed no statistically significant difference in expression levels of MALAT1 between CC and AA genotype at rs1194338 [33,34].…”
Section: Discussionmentioning
confidence: 91%